The Effect of Brain-Based Learning toward Students’ Speaking Skills - Syahbandi, Lalu Febryan (JOLLT Journal of Languages and Language Teaching, 2018)
This study was intended to find out the significant effect of Brain-Based Learning toward students’ speaking skills at SMAN 2 Praya in academic year 2017/2018. The method of the research was applied experimental research (quantitative approach). The population of the research was all the students of XI at SMAN 2 Praya and the sample of the study was 25 students consist of one classes. Based on the result of the study, it can be concluded that the use of Brain-Based Learning has positive effect toward students’ speaking skills at SMAN 2 Praya in academic year 2017/2018, in which t-test (4.664) > t-table (1.710) (0.05/90%) the df used 25. It indicated that the value of t-test was higher than t-table.